The development of the future learning skills for Graduates in TVET by using focus group discussion - Irdayanti Mat Nashir,; Ramlee Mustapha,; Mohamad Amiruddin Ismail,; Nurul Nazirah Mohd Imam Ma’arof, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study focuses on the domain to evaluate graduates’ abilities in TVET system. The reason why this study conducted is to help graduates, university and other stakeholder to overcome the employability crisis among their graduates. Thirteen experts were participated in this Focus Group Discussion. The Focus Group Discussion is a technique used in identifying, discussing and brainstorming the criteria, domain and characteristics through experts’ opinion. The approach used in this study is discussion by Webex platform. After analyzing the data findings in Focus Group Discussion using SPSS software, researcher found that out of thirteen, twelve domains reached a good consensus and agreement. This study is believed to encourage current undergraduates to develop high level future learning skills, competencies and other related abilities regarding their employability and foster training in this area by educational institutions so that can benefit their students.